Advanced VDI with VMware Horizon 7 - Oven, Peter von; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"VMware Horizon 7 delivers, protects, and manages your applications and virtual desktops and ensures the end user can access them from anywhere and at any time. It is easy to have a fundamental knowledge of VMware Horizon 7 but it is way more challenging and difficult to implement and fine-tune it according to your business needs. Our video overcomes this challenge and ensures you gain the advanced and practical knowledge required to manage and implement Horizon 7 efficiently for your organization. The video starts by demonstrating advanced installation and configuration, which will help you to customize Horizon 7 according to your business requirements. Then you'll delve into the latest features of Horizon 7 such as just-in-time delivery with instant clone; modernized life cycle management, which ensures faster application delivery; better user experience; smart policies, in order to improve security; and many more. This advanced-level video will teach you to deliver virtual desktops and applications through a single platform, multiple deployment scenarios, Horizon client and agent security, integration with third-party software, best practices, and troubleshooting techniques."--Resource description page.
Title from resource description page (Safari, viewed April 18, 2017).
Presenter, Peter von Oven.
Keywords: VMware; Virtual computer systems; Electronic books